A poverty-sensitive scorecard to prioritize lending and grant allocation: Evidence from Central America - Hernandez, Manuel A.; Torero, Máximo (International Food Policy Research Institute, 2016)
Development projects are generally subject to a potential tradeoff between sustainability and poverty reduction. Grants are also commonly assigned without a standardized criterion. This paper proposes an innovative scoring tool that combines both a risk and poverty scorecard to prioritize lending and grant allocation. We implement and test the instrument through a competitive fund for demand-driven projects in Central America intended to better link smallholder farmers to markets and improve their welfare. The evaluation results show that the highest-ranked projects generally have a larger economic impact on their beneficiaries than lower-ranked projects. We observe a larger effect on income, access to credit,and access to local markets, and the relative differences are stronger over time. The proposed scorecard tool is intended to better ensure the accountability and sustainability of development funds and can be easily adapted to different contexts